Exogenous salicylic acid treatment enhances the disease resistance of Panax vietnamensis by regulating secondary metabolite production - Hou, Jiae; Ai, Mingtao; Li, Jianbin; Cui, Xiuming; Liu, Yuan; Yang, Qian (Frontiers in Plant Science, 2024)
Salicylic acid (SA) is a phenolic compound widely found in plants. It plays a key role in exerting plant disease resistance. Panax vietnamensis Ha & Grushv., a valuable medicinal plant, contains high levels of phenolic compounds, which contribute significantly to the resilience of the plant against stress. However, the precise role of SA in regulating the synthesis of secondary metabolites in P. vietnamensis remains elusive. Here, two-year-old P. vietnamensis seedlings were treated with exogenous SA. We systematically assessed the changes in the physiological parameters of SA-treated P. vietnamensis leaves, employing transcriptome and metabolome analyses to elucidate the underlying mechanisms. Our results revealed a significant improvement of the plant's antioxidant capacity at 6 h post-treatment. Furthermore, exogenous SA treatment promoted the biosynthesis of lignin and flavonoids such as rutin, coumarin, and cyanidin. In addition, it increased the levels of endogenous SA and jasmonic acid (JA), promoting the disease resistance of the plants. Thus, SA pretreatment enhanced the defense of P. vietnamensis against pathogens. Overall, our study provided novel insights into the potential molecular mechanisms underlying SA-mediated biosynthesis of secondary metabolites. Furthermore, our results provided a theoretical foundation for optimizing the cultivation practices of P. vietnamensis and the application of SA as a plant immunomodulator.